Buyer–supplier relationships in IT outsourcing: consultants’ perspective - Martins, A. L.; Duarte, H.; Costa, D. (International Journal of Logistics Management, 2018)
Purpose Supply chain relationships have often been analysed from the macro-perspective of the companies involved, but there is less evidence of how relationships relate to the micro-perspective of persons involved. The purpose of this paper is to investigate, in IT outsourcing (ITO), how the buyer–supplier relationship type strengthens buyer performance from the perspective of consultants. Design/methodology/approach IT consultants were surveyed, and analysis was performed considering the aggregated values of variables that characterise buyer–supplier relationships adjusted to ITO. Findings The results show that strategic relationships are associated with higher supplier investment in relational management than in transactional ones. Similarly, in this type of relationship, higher levels of trust are linked to the recognition of more activities shared between parties involved than in transactional relationships. The improvement of supplier development by buyers was also found to improve buyers’ performance. Research limitations/implications The model proposed here was developed for nonspecific industries but tested in the context of ITO. Further research should be undertaken to broaden generalisability. Originality/value The paper provides an understanding of the influence of the buyer–supplier relationship type on buyer performance based both on relational management and, more specifically, how the formal dimension of supplier development can also contribute to performance. ITO is increasing worldwide, and relational management affects outsourcing outcomes in broad supply chain integration. This analysis is usually visited from buyer and supplier perspectives using decision makers. This paper assesses it from the perspective of consultants.